Factors influencing customer’s purchase intention towards Halal cosmetics among young adults / Azaliana Ayob - Ayob, Azaliana (Faculty of Business and Management, 2019)
Muslim population has been increasing globally over the years. Increasing along with it is the awareness of halal consumption. Many Muslims are becoming more aware towards the Halal idea and it has now not limited to food segment but non-food segment as well such as personal care, toiletries, fragrance and cosmetic products. In Malaysia, it can be observed of the palpable increasing demand for cosmetics product and due to the advancement of technology, knowledge and resources, cosmetics industry can be seen to be a major growing sector for the Halal industries. Multiple studies have been conducted to investigate the determinants of customer’s intention to purchase or Halal cosmetics. The main objective for this research is to identify the factors influencing customer’s purchase intention towards Halal cosmetics. The elements that will be examined are attitude, subjective norm, perceived behavioural control and brand awareness. Convenient sampling technique was used and questionnaires were distributed to more than 300 respondents from UiTM Kampus Bandaraya through internet survey. Subsequently, data collected were transferred into the SPSS program and analysed. The data went through several statistical analyses such as the frequency analysis, reliability analysis, descriptive analysis, Pearson correlation analysis and multiple regression analysis. The outcome was confirmed that all of the variables are positively related to customer’s purchase intention towards Halal cosmetics. All in all, the findings of this research study can be beneficial to the entities involved in Halal cosmetic industry and future researcher.